CONTRIBUTION OF INTERNAL AUDIT IN IMPROVING THE QUALITY OF ACCOUNTING INFORMATION IN COMMERCIAL BANKS IN BASRA - Hayder Jerri Mohsin; Mohammed Qasim Yahya (Scholar Express Journals, 2023)
The goal of this study is to show the role of internal audit and its dimensions (comprehensive assessment of internal audit, development of a comprehensive training program, work environment, supervision, As well as means of improving the quality and scope of accounting information through conducting theoretical and field investigations on (the efficiency, effectiveness and credibility of accounting information and its role in reducing risks). The study comprised a quantitative examination of the data from commercial banks in the study nation's capital, Baghdad, which had (10) individuals, the research sample included a group of (140) employees from these institutions. The research is built on a strong basis to expose these institutions' policies regarding the contribution internal audit makes to raising the caliber of accounting information. The purpose of the study was to investigate the link and correlation between the independent variable, which represented internal audit, and the characteristics of the dependent variable, which was the quality of accounting information. Using the SPSS program's statistical methodologies for data processing. The outcomes of the statistical analysis of the information gathered through the specially designed questionnaire demonstrate that there is a relationship and influence between internal audit and its components. (Comprehensive evaluation of internal audit, The outcomes of the statistical analysis of the information gathered through the designed for this purpose questionnaire demonstrate that there is a relationship and influence between internal audit and its components of (a comprehensive training program, work environment, follow-up, and control) As criteria for measuring the quality of accounting information, the efficacy of accounting information, dependability of accounting information, and the significance of accounting information in risk mitigation are offered, The degree to which a group of internal auditor characteristics, know-how, and abilities contribute to enhancing the caliber of accounting information is the dependent variable
Keywords: Internal Audit; accounting Information